Lower level wind flow over the Indian Ocean during the onset of Monsoon -1987 (MAUSAM, 1989)
INSAT-1B low level. cloud motion vectors (CMVs) extracted daily over some part of the Indian Ocean during the period 28 May to 7 June 1987 were subjected to a new quality control technique. The accepted winds were analysed in conjunction with INSAT imagery to understand the wind flow prior to and just after the onset of the southwest monsoon over Kerala. It was observed that 2-3 days before the actual date of onset there was strong cross-equatorial flow and strengthening of the winds in southeast Arabian Sea ,as well as off the Somali coast. An east-west trough with embedded vortices moved northward in south Arabian Sea systematically for about 4 days prior to the day of onset, thereby establishing the southwest monsoon current over and off Kerala coast. After the setting in of the monsoon the CMV clusters very clearly showed the strong monsoon current over the ocean